FOOD SECURITY IN THE UPPER EAST REGION OF GHANA: A SITUATIONAL ANALYSIS - Alhassan, S. (UDS International Journal of Development, 2016)
Despite significant progress made by the government of Ghana in recent times in reducing poverty incidence in rural areas of the country there still remain some challenges in food access, use and availability. The experience of less developed countries shows that food security has often been negatively affected by climate variability, natural disasters and socio-political instability. The main research question is whether or not poverty reduction always brings about increased food security. This paper examines the food situation in the Upper East Region of Ghana with respect to both irrigated and non-irrigated smallholder farmers with focus on food sources and causes of food insecurity and food insecurity coping strategies. Results of in-depth interviews and desk studies reveal that poverty reduction is not always accompanied by increased food security. However, increased access to agricultural water through small-scale irrigation schemes has a positive impact on the food security status of rural households. Irrigation farmers’ inability to expand their farming ventures is due to a number of constraints, prominent among them are difficulty in securing credit to buy inputs such as seeds, fertilizer and agro-chemicals; high disease infestation of irrigated crops (eg nematodes) and poor maintenance of the schemes. The policy implication is that increased access to food security requires the joint support of government, civil society organisations (NGOs) and the private sector. Key words: Food Security, Irrigation and Poverty